Bioactives of the essential oil from the leaves of Eugenia pyriformis Cambess (Myrtaceae) on the effects of tobacco - Medeiros, Jaqueline Pavelegini de (2024)
Lung cancer is the most commonly diagnosed and the main cause of cancer death, usually related to cigarette smoking. Furthermore, the microbiota of people exposed to cigarette smoke can be modified, making it difficult to eliminate opportunistic microorganisms. The leaves of Eugenia pyriformis are a by-product of fruit production and, to date, there have been no studies addressing the antiproliferative, anti-inflammatory, and antimicrobial activities. Objective Investigate the antimicrobial, Nitric Oxide (NO)-production inhibition, and antiproliferative activities of the essential oil from E. pyriformis leaves and its possible effect on the treatment and prevention of damage caused by tobacco. Methods The essential oil (EO) was obtained by hydrodistillation (3 h). Its chemical composition was investigated by GC-MS. It was proposed to investigate antiproliferative activity against human tumor cell lines, namely, breast adenocarcinoma (MCF-7), lung (NCI-H460), cervical (HeLa), and hepatocellular (HepG2) carcinomas. A non-tumor primary culture from pig liver (PLP2) was also tested. The EO capacity to inhibit nitric oxide (NO) production was evaluated by a lipopolysaccharide stimulated murine macrophage cell line. Antibacterial and antifungal activities against opportunistic pathogens were investigated against seven strains of bacteria and eight fungi. Results The results indicated the presence of 23 compounds in the essential oil, the majority were spathulenol (45.63%) and beta-caryophyllene oxide (12.72%). Leaf EO provided 50% inhibition of nitric oxide production at a concentration of 92.04 mu g mL(-1). The EO also demonstrated antiproliferative activity against all human tumor cell lines studied, with GI50 values comprised between 270.86 and 337.25 mu g mL(-1). The essential oil showed antimicrobial potential against the bacteria Listeria monocytogenes (Murray et al.) Pirie (NCTC 7973) and Salmonella Typhimurium ATCC 13311 (MIC 1870 mu g mL(-1)) and fungi Aspergillus versicolor ATCC 11730, Aspergillus ochraceus ATCC 12066, Penicillium ochrochloron ATCC 90288, Penicillium verrucosum var. cyclopium (Westling) Samson, Stolk & Hadlok (food isolate) (MIC 1870 mu g mL(-1)) and Trichoderma viride Pers. IAM 5061 (1,400 mu g mL(-1)). Conclusion The demonstrated anti-inflammatory, antiproliferative, and antimicrobial activities in the leaves of E. pyriformis can add value to the production chain of this plant, being a possible option for preventing and combating cancer, including lung cancer.